Screen Fast, Screen Faster: A Pilot Study to Screen for Depressive Symptoms Using the Beck Depression Inventory Fast Screen in Parkinson's Disease With Mild Cognitive Impairment - Elben, Saskia; Dimenshteyn, Karina; Trenado, Carlos; Folkerts, Ann-Kristin; Ophey, Anja; Sulzer, Patricia; Becker, Sara; Schmidt, Nele; Tödt, Inken; Witt, Karsten; Liepelt-Scarfone, Inga; Yilmaz, Rezzak; et al. (Frontiers in Neurology, 2021)
Objective Depressive symptoms have a high prevalence in patients with Parkinson’s disease (PD) and are associated with cognitive dysfunction. Especially in PD with mild cognitive impairment (MCI), a time-efficient and valid instrument for the assessment of depression primarily focusing on psychological symptoms and disregarding confounding somatic symptoms is needed. We performed an examination of the psychometric properties of the Beck Depression Inventory II (BDI-II) and the Beck Depression Inventory Fast Screen (BDI-FS). Methods The sample consisted of 64 patients (22 females and 42 males, mean age: 67.27 years (SD=7.32)). Depressive symptoms were measured in a cohort of PD patients with MCI. For the BDI-II and BDI-FS the psychometric concepts of internal consistency, convergent validity and diagnostic agreement were assessed. Results Patients gave higher ratings on test items addressing somatic symptoms than those addressing non-somatic ones. The correlation between the absolute total scores of the BDI-II and the BDI-FS was significant (r=0.91, p<0.001), which indicated convergent validity. The Cronbach’s alpha values indicated adequate internal consistencies for both measures (BDI-II: 0.84; BDI-FS: 0.78). There was a higher than chance level agreement of diagnoses of the two questionnaires, measured by Cohen’s kappa (0.58, p<0.001). The agreements between previous diagnosis of depression and the diagnoses of the BDI-II/BDI-FS were also significantly higher than chance level (BDI-II: 0.34, p=0.007, BDI-FS: 0.39, p=0.002). Additional AUC analysis across different cutoffs showed that performance of BDI-FS was better than BDI-II, supporting the observation of an equivalent or better performance of BDI-FS than BDI-II. Importantly, AUC analysis confirmed that a cutoff =4 for BDI-FS was suitable in the considered sample of patients with PD-MCI. Discussion In a cohort of PD-MCI, the BDI-FS demonstrates adequate psychometric properties in comparison to the BDI-II and can be used as a screening measure for assessing depression in cognitively impaired PD patients, focusing solely on psychological symptoms. Still, further research is needed to validate this instrument.